The genome sequence of the lime hawk-moth, Mimas tiliae (Linnaeus, 1758) - Boyes, D; Holland, PWH (F1000Research, 2021)
We present a genome assembly from an individual male Mimas tiliae (the lime hawk-moth; Arthropoda; Insecta; Lepidoptera; Sphingidae). The genome sequence is 478 megabases in span. The complete assembly is scaffolded into 29 chromosomal pseudomolecules, with the Z sex chromosome assembled.